MENAKAR METODE PEMAHAMAN HADIS YUSUF AL-QARADAWI TERHADAP HADIS-HADIS RUKYAT HILAL: KAJIAN INTERDISIPLINER STUDI ASTRONOMI DAN STUDI HADIS - Abdul Mufid (Jurnal Studi Islam dan Sosial, 2019)
The highest reference for Muslims in understanding Islamic law is the Qur'an and hadith with the hadith ranked second after the Qur'an. In the history of Islam, hadith is a source of polemic in Islamic law. Among the problems that still occur today are understanding of the “observation of crescent” traditions related to the determination of the beginning of the lunar month. The discourse about the difference in the determination of the beginning of the Hijri month is a consequence of the different points of view of understanding the “observation of crescent” traditions. Therefore the method of understanding the hadith on the “observation of crescent” is something urgent to study. The final conclusion of this paper research process can be seen that the implications of Yusuf al-Qaradawi's understanding of the “observation of crescent” traditions are the hope of al-Qaradawi for the realization of the unification of fasting and the feast of Muslims in Europe on a priority basis, not the unification of all Muslims on earth.